The Effects of Short- and Long-Term Therapy on Laboratory Parameters Among Pediatric Patients with Epilepsy Receiving Antiepileptic Drug Monotherapy - Hilal Aydın; İbrahim Hakan Bucak; Mehmet Geyik (Archives of Epilepsy, 2022)

(untitled)
Objective:To evaluate the effect of short- and long-term treatment on laboratory parameters in patients diagnosed with epilepsy in childhood and receiving monotherapy (carbamazepine, valproic acid, phenobarbital, levetiracetam).Methods:This study included a total of 258 patients who were admitted to Adiyaman University pediatric neurology clinic between 1 October 2017 and 1 June 2019, diagnosed with epilepsy, and received monotherapy. Hematological, biochemical, and hormonal profiles were compared in the third and nine months following the initiation of monotherapy.Results:Of the patients, 115 (44.57%) were female and 143 (55.43%) were male. The mean age was 8.33 ± 3.51 (0-17) years. Examination of biochemical parameters showed that there was a statistically significant difference in creatinine levels in patients using levetiracetam and phenobarbital (p = 0.009, p = 0.031); calcium levels in patients using valproic acid (p = 0.002); and alanine aminotransferase levels in patients using carbamazepine (p = 0.045). Considering hematological parameters, a statistically significant difference was observed in white blood cell count levels in patients receiving valproic acid (p = 0.005); hemoglobin and hematocrit levels in those receiving carbamazepine (p = 0.010, p = 0.042); and platelet levels in patients receiving phenobarbital (p = 0.037). In all patients receiving monotherapy, there was no statistically significant difference between hormonal parameters (folate, 25-OH D3, vitamin B12, free t4, and TSH) measured in the third and ninth months.Conclusions:We recommend that AED therapy should be checked routinely to investigate the effects of treatment on hormonal, biochemical, and hematological parameters.